Terapéutica antimicrobiana y su relación con el desarrollo de la neumonía en pacientes ventilados de la terapia intensiva hospital IESS Babahoyo, Los Ríos, septiembre 2017 a febrero 2018 - Pisco Carpio, Erick Alexander (2018)
The research has required a quantitative approach and a field investigation, to know the background, and the evolution of pneumonia and to know how it relates to antimicrobial therapy in patients ventilated from intensive therapy. Through the research carried out in the IESS Babahoyo hospital, it will allow us to know the relationship that antimicrobial therapy has with the development of pneumonia in patients ventilated from intensive therapy, when requesting the corresponding permits to enter the study area by means of The approved application was reviewed throughout the clinical history of patients undergoing ventilation and who developed pneumonia who were admitted to the IESS Babahoyo los Ríos hospital during the study period. They also asked questions directly to doctors and nurses to collect information after the review was made to the medical records and the various reports of the therapist in which it was obtained that during the study period 107 patients were admitted to the hospital. which only found 10 cases of pneumonia associated with mechanical ventilation and the rest of patients with other diagnoses in which relevant data were collected to verify the relationship between pneumonia associated with mechanical ventilation and antimicrobial therapy in the intensive therapy . In the 10 cases found, it was shown in the tabulation that the level of mortality due to pneumonia is low due to the good professionalism of each nurse-therapist and doctors since they are prepared to prevent patients undergoing mechanical ventilation from contracting pneumonia.